Assessment of client core issues - Halstead, Richard W. (Alexandria, Va. : American Counseling Association, 2006)
Instructs counselors on how to better recognize, understand, and treat clients' underlying problems, or deeper issues, in order to provide the most effective counseling services available.
An introduction to client core issues -- Conceptual foundations for understanding client core issues -- Assessment of core issues and the nature of the client's living story -- Designing the counseling intervention : framing the client's living story -- The case of Sue -- Incorporating the core issues framework in counseling practice.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Counseling; Counseling; Counseling -- methods; Electronic books